Analysis of predictive factors of unforeseen nodal metastases in resected clinical stage I NSCLC - Gallina, Filippo Tommaso; Marinelli, Daniele; Tajè, Riccardo; Forcella, Daniele; Alessandrini, Gabriele; Cecere, Fabiana Letizia; Fusco, Francesca; Visca, Paolo; Sperduti, Isabella; Ambrogi, Vincenzo; Cappuzzo, Federico; Melis, Enrico; et al. (Frontiers in Oncology, 2023)
Background Despite notable advances made in preoperative staging, unexpected nodal metastases after surgery are still significantly detected. In this study we aim to analyze the upstaging rate in patients with clinical stage I NSCLC without evidence of nodal disease in the preoperative staging who underwent lobectomy and radical lymphadenectomy. Methods Patients who underwent lobectomy and systematic lymphadenectomy for clinical stage I NSCLC were evaluated. Exclusion criteria included the neoadjuvant treatment, incomplete resection and no adherence to preoperative guidelines. Results A total of 297 patients were included in the study. 159 patients were female, and the median age was 68 (61 - 73). The variables that showed a significant correlation with the upstaging rate at the univariate analysis were the number of resected lymph nodes and micropapillar/solid adenocar-cinoma subtype. This result was confirmed in the multivariate analysis with a OR= 2.545 (95%CI 1.136-5.701; p=0.02) for the number of resected lymph nodes and a OR=2.717 (95%CI 1.256-5.875; p=0.01) for the high-grade pattern of adenocarcinoma. Conclusion Our results showed that in a homogeneous cohort of patients with clinical stage I NSCLC, the number of resected lymph nodes and the histological subtype of adenocarcinoma can significantly be associated with nodal metastasis.